Schools for pre-adolescents: a comparative study of the 9-13 middle school in Dorset - Seymour, Kathleen (2012)
When they first appeared on England’s educational landscape, middle schools held the promise of providing a schooling environment ideally suited to the needs of pre-adolescents. This research aims to assess how far they have fulfilled that promise.